2014
DOI: 10.1016/j.nano.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/neu targeted delivery of a nanoprobe enables dual photoacoustic and fluorescence tomography of ovarian cancer

Abstract: Development of sensitive and specific imaging approaches for the detection of ovarian cancer holds great promise for improving survival of ovarian cancer patients. Here we describe a dual-modality photoacoustic and fluorescence molecular tomography (PAT/FMT) approach in combination with a targeted imaging probe for three-dimensional imaging of ovarian tumors in mice. We found that the selective accumulation of the HER-2/neu targeted magnetic iron oxide nanoparticles (IONPs) led to about 5-fold contrast enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…was specifically targeted to primary and metastatic tumors in an orthotopic human ovarian cancer xenograft model. These tumors produced strong imaging signals for FMT, photoacoustic tomography (PAT) and magnetic resonance imaging (MRI) [21,30]. In this study, two tumors were also well detected using FMTPen.…”
Section: Animal Experimentsmentioning
confidence: 60%
“…was specifically targeted to primary and metastatic tumors in an orthotopic human ovarian cancer xenograft model. These tumors produced strong imaging signals for FMT, photoacoustic tomography (PAT) and magnetic resonance imaging (MRI) [21,30]. In this study, two tumors were also well detected using FMTPen.…”
Section: Animal Experimentsmentioning
confidence: 60%
“…In particular, superparamagnetic iron oxide nanoparticles (SPIO) were studied as agents for lymph node staging in a rat model of prostate cancer, where the lack of uptake in metastases compared with healthy tissue provided negative optoacoustic image contrast in specimens imaged ex vivo (69). HER-2/neu-targeted iron oxide nanoparticles have been investigated for imaging of ovarian cancer in a mouse model (70). However, iron oxide particles typically do not display high optical absorption in the NIR, which makes in vivo detection highly challenging.…”
Section: Exogenous Contrastmentioning
confidence: 99%
“…11 However, in vivo PA tumor imaging requires site-selective IONP delivery because, compared with organic dyes, light absorption of IONPs at near-infrared wavelength is relatively low. 12 Some groups reported the method of delivering IONPs conjugated with fluorescent organic dye to tumors using targeting moieties, such as affibody 13 , and amino-terminal fragments. 14 However, in these reports, IONPs were used as delivering scaffolds, and not as near-infrared light absorbers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Lei et al have reported in vivo tumor PA imaging using IONPs conjugated with fluorescent dye (NIR-830 dye) and anti-HER2 antibody 13. In this paper, fluorescent dye was used to increase absorption coefficient for PA imaging along with acquisition of fluorescence imaging.…”
mentioning
confidence: 99%